Deep Learning in Dance Education : A Strategy for Instilling Character Values in Today's Elementary School Children - Komalasari, Heni; Barnas, Beben; Sabaria, Ria (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a character education model based on a deep learning approach in traditional dance learning for elementary school students in both urban and rural areas of Bandung. The Research and Development (R&D) method is employed, adapting the steps proposed by Borg & Gall, which include preliminary study, planning, model development, limited trial, revision, wider trial, and final model refinement. The model is structured around three core phases in the learning process: movement meaning exploration, value reflection, and expression through dance creation. Data collection utilizes observation sheets, interview guides, character assessment rubrics, and documentation, while analysis employs qualitative techniques (data reduction, presentation, and conclusion drawing) combined with descriptive statistics. Implementation of the model over three sessions in two elementary schools resulted in significant improvements across four key character aspects: independence, collaboration, responsibility, and critical thinking. The deep learning approach has proven effective in fostering students' value awareness through reflective, meaningful, and contextual learning experiences. This model is expected to serve as a strategic alternative for embedding character values into traditional dance instruction at the elementary school level.